Anesthesia and the fetus - Reynolds, Felicity; Halpern, Stephen
This book covers all aspects of anesthesia affecting the fetus throughout in utero life. The book comprises three sections looking at: 1) endpoints for fetal and neonatal outcomes, 2) anesthetic interventions that may affect these endpoint variables, and 3) confounding variables which may modify the effects of anesthesia and analgesia on outcomes. A concise, pratical guide backed up by theory, it also discusses wider ethical and legal considerations. With increasing uses of anesthesia throughout pregancy, this book makes anesthetists and obstetricians aware of the potential affects of anesthetics on fetal development and outcomes"--Provided by publisher